ANALISIS QUALITY OF SERVICE (QOS) JARINGAN INTERNET BERBASIS WIRELESS LOCAL AREA NETWORK (WLAN) PADA PT. SAMMA JAYA PERKASA - Ayudilla Laili Ramadian; Luthfi Indriyani Indriyani (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2023)
A wireless network is a set of computers that are interconnected with each other. To create a computer network, because of the many needs and communications accessed until network performance must be in good condition. When building a network, it is mandatory to consider Quality of Service (QoS). Quality of Service (QoS) is an aspect of performance that affects user satisfaction in using a service. The quality of this service is affected by network performance, including throughput, packet loss, delays, and time fluctuations (Jitter). Quality of Service (QoS) parameters consist of throughput, packet loss, delay, and jitter according to THYPON standards. At PT. Samma Jaya Perkasa for smooth work that requires an internet network. Internet service at PT. Samma Jaya Perkasa uses an Internet Service Provider (ISP) from Indihome and a rented bandwidth of 30Mbps. Therefore, measurement is needed to recognize the quality of services provided—the results of Quality of Service (QoS) measurements on the internet network of PT. Samma Jaya Perkasa can be known for its throughput of "1363.6 kbs", packet loss of "1.533%", delay of "4.92 ms", and jitter of "5 ms" until it can be concluded that the internet network at PT. Samma Jaya Perkasa for THIPON standards is included in the type of Good.